Liver transplantation for alcoholic hepatitis: A systematic review with meta-analysis. - Astrid Marot; Margaux Dubois; Eric Trépo; Christophe Moreno; Pierre Deltenre (PLoS ONE)
Background The rate of alcohol relapse among patients who underwent liver transplantation for alcoholic hepatitis (AH) is not precisely known. Aim Synthesize the available evidence on liver transplantation for AH to assess alcohol relapse and 6-month survival. Methods Meta-analysis of trials evaluating liver transplantation for AH, either clinically severe or diagnosed on the explant. Results Eleven studies were included. The pooled estimate rate for alcohol relapse was 0.22 (95% CI = 0.12-0.36) in overall analysis with high heterogeneity between studies (I2 = 76%), 0.20 (95% CI = 0.07-0.43) in the subgroup analysis including patients with clinically severe AH (I2 = 84%), 0.14 (95% CI = 0.08-0.23) among patients with clinically severe AH in sensitivity analysis excluding the discrepant studies that did not use stringent selection criteria for liver transplantation (I2 = 0%), and 0.15 (95% CI = 0.07-0.27) for recurrent harmful alcohol consumption among patients with clinically severe AH (I2 = 3%). The risk of alcohol relapse was not different between AH transplanted patients and patients with alcoholic cirrhosis who underwent elective liver transplantation in sensitivity analysis excluding the discrepant studies (OR = 1.68, 95%CI = 0.79-3.58, p = 0.2, I2 = 16%). The pooled estimate rate for 6-month survival was 0.85 (95% CI = 0.77-0.91, I2 = 49%), and 0.80 among patients transplanted for clinically severe AH (95% CI = 0.69-0.88, I2 = 30%). AH transplanted patients had similar 6-month survival to patients with alcoholic cirrhosis who underwent elective liver transplantation (OR = 2.00, 95% CI = 0.95-4.23, p = 0.07, I2 = 0%). Conclusion Using stringent selection criteria, 14% of patients with clinically severe AH have alcohol relapse after liver transplantation. The percentage of alcohol relapse of AH transplanted patients is similar than that of patients who underwent elective liver transplantation.